2015
DOI: 10.1063/1.4905905
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic corrections for screening effects on the energies of hydrogen-like atoms embedded in plasmas

Abstract: The influence of relativistic and plasma screening effects on energies of hydrogen-like atoms embedded in plasmas has been studied. The Dirac equation with a more general exponential cosine screened potential has been solved numerically and perturbatively, by employing the direct perturbation theory. Properties of spectra corresponding to bound states and to different sets of the potential parameters have been studied both in nonrelativistic and relativistic approximations. Binding energies, fine-structure spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
4
9
0
Order By: Relevance
“…It is noted from Table 2 and comparison in the Supporting Information that the present results show excellent agreement with the calculations of Poszwa [54]. For further comparison, we list in Table 3 the present and Chaudhuri et al [56]'s first‐order relativistic corrections and the fully relativistic calculation of Poszwa and Bahar [55] for the ground state of Ca 19+ in ECSCP. The present relativistic‐corrected energies are in better agreement with the fully relativistic results of Poszwa and Bahar [55] in all cases.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…It is noted from Table 2 and comparison in the Supporting Information that the present results show excellent agreement with the calculations of Poszwa [54]. For further comparison, we list in Table 3 the present and Chaudhuri et al [56]'s first‐order relativistic corrections and the fully relativistic calculation of Poszwa and Bahar [55] for the ground state of Ca 19+ in ECSCP. The present relativistic‐corrected energies are in better agreement with the fully relativistic results of Poszwa and Bahar [55] in all cases.…”
Section: Resultssupporting
confidence: 79%
“…Input parameters of N = 400 and L = hri are used in the present GPS calculations and the reported numerical values are fully converged in all digits shown in the tables. It is found that our results are in excellent agreement with the previous predictions when they are available and, furthermore, the agreement in ECSCP demonstrates that the first-order direct perturbation approximation is well applied for low-Z hydrogen-like ions [54,55].…”
Section: Relativistic Correctionssupporting
confidence: 88%
See 3 more Smart Citations